2022
DOI: 10.1039/d1ta08981a
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-ion storage behavior of microstructure-engineered hard carbons

Abstract: A distinctive solid-solution potassium-ion intercalation behavior of disordered graphitic carbon materials was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Stage I intercalation compounds are known to have a golden color, whereas the stage II, III, and IV intercalation compounds exhibit a blue color. [30][31][32] The fully lithiated hard carbon electrodes reveal that the black-colored pristine electrode transforms into dark blue colors for HC1200, HC1600, HC2000, and HC2400, and dark yellow color for HC2800 (Figure S21a-e, Supporting Information). The color change indicates that lithium-ion intercalation reaction happens in all the samples, where lithium intercalation compounds of stage II, III, and IV were formed for HC1200, HC1600, HC2000, and HC2400, whereas a stage I intercalation compound is mainly formed for HC2800.…”
Section: Resultsmentioning
confidence: 99%
“…Stage I intercalation compounds are known to have a golden color, whereas the stage II, III, and IV intercalation compounds exhibit a blue color. [30][31][32] The fully lithiated hard carbon electrodes reveal that the black-colored pristine electrode transforms into dark blue colors for HC1200, HC1600, HC2000, and HC2400, and dark yellow color for HC2800 (Figure S21a-e, Supporting Information). The color change indicates that lithium-ion intercalation reaction happens in all the samples, where lithium intercalation compounds of stage II, III, and IV were formed for HC1200, HC1600, HC2000, and HC2400, whereas a stage I intercalation compound is mainly formed for HC2800.…”
Section: Resultsmentioning
confidence: 99%
“…Kim and coworkers investigated the correlation between microstructure and potassium-ions storage behavior in hard carbons. [13] They concluded that a few nanometer-sized graphitic domains and expanded d-spacing (>3.5 Å) in disordered graphitic structures can trigger fast and stable potassium-ion intercalation. Similarly, Alvin et al established the relationship between the intercalation sites and low-potential-plateau capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Hard carbon materials with local graphitic nanodomains are mainly synthesized by controlling carbonization temperature, while high temperature would induce the closed domains that are inaccessible for K + (de)intercalation. [ 10b,11e,13 ] Thus, an effective approach is expected to fabricate hard carbon materials with a crystalline structure of short‐range order and large interlayer spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that stable GICs may not be formed, and the GICs are directly related to the degree of graphitization of hard carbon materials. 71 In the trace of highly graphitized sample (DGC-2000), significant formation of KC 8 (stage I) was observed at the end of complete potassiation. Surprisingly, two-phase intercalation products, KC 48 (stage IV), KC 36 (Stage III) and KC 24 (Stage II), were separated using the in situ XRD pattern signal during the electrochemical cycle of DGC-2800 (Fig.…”
Section: Intercalation Mechanismmentioning
confidence: 95%